Frequency and Risk Factors of Acute Kidney Injury (AKI) in Patients Admitted to the Intensive Care Unit (ICU) - Ahmed , Sarfaraz; Hanif , Shamimah; Asmat , Fauzia; Raheem , Abdul; Khan , Sobaidar; Shah , Firasat Ullah; Malik , Abdul (Indus Journal of Bioscience Research, 2025)
Background: In critically sick patients, especially those hospitalized to intensive care units (ICUs), acute kidney damage (AKI) is a serious consequence. It is distinguished by an abrupt deterioration in renal function, which raises morbidity and mortality. Because of its high prevalence and dismal prognosis, AKI continues to be a significant issue despite improvements in critical care. Objective: The objective of this study is to identify the risk factors and frequency of AKI in patients in the intensive care unit. It focusses on determining the main causes, including comorbidities, nephrotoxic exposure, sepsis, and hypovolemia, and evaluating how they affect patient outcomes. Methodology: 140 participants, including ICU doctors, nephrologists, nurses, and patients, participated in a qualitative study at a tertiary care hospital. Semi-structured interviews and focus groups were used to gather data, and theme analysis was then conducted. Results: Sepsis was the main risk factor for AKI in intensive care unit patients, followed by hypovolemia, nephrotoxic medications, and chronic illnesses. AKI is a leading cause of intensive care unit death and chronic renal impairment, and delayed identification and intervention worsened outcomes. Conclusion: lowering the prevalence of AKI requires early recognition, risk assessment, and preventive actions. Enhancing sepsis control, minimizing nephrotoxins, and optimizing fluid management can all improve survival and lower sequelae. Future studies should investigate tailored therapies for patients in critical condition and improve biomarkers.